(3JaGYd eOjQj GdeOGQS GdKGfhjI GdQSejI eY GdefGgL GdJYdjejI GdLOjOI aj dHfGfs - (3fGUQ GdOjf, QGZOIs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdJQHjI, GdYeGOIs, 2001)
(3JfGhdJ gPg GdOQGSI GdefGgL GdJYdjejI GdLOjOI aj dHfGf HGYJHGQ Cf MOK EWdGbgG bO dGbi CgejI cHQi hGgJeGekG ef bHd eNJda aFGJ hgjFGJ GdeLJeY, eMGhdI GdcTa Yf LghRjI GdeOGQS GdQSejI dGSJbHGd gPG GdJZjjQ, hHNGUI eOjQhgG, MjK GfMUQ GdehVhY HeOi JaGYd GdeOjQjf eY GdefGgL GdLOjOI deG dgPG GdJaGYd ef OhQ eQcRj aj cjajI JWHjbgG(B. (3dJMbjb Pdc WQMJ GdOQGSI fhYjf ef GdCSFdI(B: 1) (3cja Jqe UfY GdefGgL GdLOjOI, heG ehbY eOjQj GdeOGQS ef gPg GdUfGYI hJWHjbgG? (B2) (3cja JaGYd GdeOjQhf eY GdefGgL GdLOjOI? dPdc GfMUQ gOa GdOQGSI aj cTa GdfbGH Yf MOhO JaGYd eOjQj GdeOGQS eY GdefGgL GdLOjOI(B. (3EYJeOJ GdGSJeGQI cCOGI ddGSJbUGA GdejOGfj MjK JchfJ YjfI GdOQGSI ef MhGdi fUa GdKGfhjGJ GdQSejI aj dHfGf HfSH eJbGQHI Ydi GdeMGaXGJ GdNeS, acGf YOO GdGSJeGQGJ GdehRYI Ydi GdKGfhjGJ GdQSejI (B117 (3GSJeGQI CeG GdGSJeGQGJ GdJj Je GSJdGegG agj (B88 (3GSJeGQI(B. (3HYO JMdjd GdGSJeGQGJ hGdMUhd Ydi GdeYWjGJ Jqe GdJhUd Edi fJGFL YqOI efgG(B: 1) (3Ef eTGQcI GdeOjQjf aj GdYedjGJ GdCSGSjI dJZjjQ GdefGgL GdJYdjejI cGfJ VFjdI LOG, hbO GfYcSJ gPg GdeTGQcI GdVFjdI Ydi eSJhi GWdGYge hJedcge ddefGgL GdLOjOI(B. 2) (3Ef GdJfSjb eG Hjf CLgRI GdEOGQI GdJQHhjI GdQSejI aj dHfGf cGf VFjdG hZjQ cGa, hGdJhGUd Hjf GdEOGQGJ GdJQHhjI GdQSejI hGdEOGQGJ GdeOQSjI cGf VFjdG eeG OaY ZGdHjI GdeOjQjf ddGYJeGO Ydi YdGbGJge hLghOge GdTNUjI aj eYQaI TQhW heSJdReGJ GdJWHjb heMGhdI JdHjJgG(B. 3) (3ZGdHjI GdeOGQS GdKGfhjI de JJecf ef JWHjb Ch JOQjS GdehGO GdeSJMOKI NdGd GdYGe GdOQGSj GdChd dJWHjb GdefGgL GdLOjOI (B(1998/1999). (3dCSHGH YOjOI efgG YOe JLgjR ZGdHjI GdKGfhjGJ HGdTcd GdedGFe ddefGgL GdLOjOI, hYOe JCejf GdCSGJPI dJYdje gPg GdehGO aj LejY GdeOGQS, hGdGWdGY Gdbdjd deOjQj GdeOGQS Ydi ZGdHjI gPg GdehGO, hYOe GJNGP ELQGAGJ bGfhfjI JDef MSf GdJWHjb cJSgjd GdJYGbO eY gDdGA GdCSGJPI(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Curricula; Curriculum; Gestion scolaire; Public Sector Secondary Education; School management; Secteur Public Cycle Secondaire; (3GdGOGQI GdeOQSjIs; (3GdJYdje GdQSej GdeQMdI GdKGfhjIs; (3GdefGgLs